Biological Psychology - Hove, Michael J.; Martinez, Steven A. (Open textbook library., 2024)
Biological psychology is the study of the biological bases of behavior and mental processes. It explores how biological factors like genes, hormones, neurotransmitters, and brain structures influence psychological components like thoughts, emotions, memories, and actions. This free and open textbook provides a wide ranging and up-to-date introduction to the main topics and methods of biological psychology.